Monitoring and management of adverse effects associated with trastuzumab deruxtecan: a UAE-specific consensus - Dawoud, Emad; Azribi, Fathi; Chehal, Aref; Dawood, Shaheenah; Tirmazy, Syed Hammad; Hamza, Dina; Jaafar, Hassan; Marashi, Hussam (Frontiers in Oncology, 2025)
Breast cancer is the most frequently diagnosed cancer in the UAE and a leading cause of cancer-related mortality. Although early diagnosis contributes to favorable prognoses, novel treatment modalities like antibody-drug conjugates (ADCs) have significantly broadened the therapeutic landscape for patients in metastatic settings. The recognition of “HER2-low” expression as a targetable category has caused a paradigm shift in the management of breast cancer. Although initially developed to target HER2-positive breast cancer, trastuzumab deruxtecan (T-DXd), an ADC, has now also been approved to treat metastatic or unresectable HER2-low breast cancers. Despite the inherent specificity of an ADC, the risk of off-site toxicity exists and is an essential component while assessing the risk-benefit ratio of the treatment. Developing strategies to balance efficacy and safety is crucial, especially for newly approved therapies like T-DXd. Regional perspectives, cultural beliefs, and demographic factors influence treatment decisions and outcomes. The objective of this paper is to establish a UAE-specific consensus among oncologists on practical T-DXd treatment considerations and management of associated side effects. Establishing a consensus on monitoring and managing T-DXd side effects among experts can promote informed decision-making.